Profiling the Production of Antimicrobial Secondary Metabolites by Xenorhabdus khoisanae J194 Under Different Culturing Conditions - Booysen, Elzaan; Rautenbach, Marina; Stander, Marietjie A.; Dicks, Leon M. T. (Frontiers in Chemistry, 2021)
Species from the genus Xenorhabdus, endosymbiotic bacteria of Steinernema nematodes, produce several antibacterial and antifungal compounds, some of which are anti-parasitic. In this study, we report on the effect growth conditions have on the production of antimicrobial compounds produced by Xenorhabdus khoisanae J194. The strain was cultured in aerated and non-aerated broth, respectively, and on solid media. Production of antimicrobial compounds was detected after 24 h of growth in liquid media, with highest levels recorded after 96 h. Highest antimicrobial activity was obtained from cells cultured on solid media. By using ultraperformance liquid chromatography linked to mass spectrometry and HPLC, a plethora of known Xenorhabdus compounds were identified. These compounds are the PAX lipopeptides (PAX 1′, PAX 3′, PAX 5, and PAX 7E), xenocoumacins and xenoamicins. Differences observed in the MS-MS fractionation patterns collected in this study, when compared to previous studies indicated that this strain produces novel xenoamicins. Three novel antimicrobial compounds, khoicin, xenopep and rhabdin, were identified and structurally characterized based on MS-MS fractionation patterns, amino acid analysis and whole genome analysis. The various compounds produced under the three different conditions indicates that the secondary metabolism of X. khoisanae J194 may be regulated by oxygen, water activity or both. Based on these findings X. khoisanae J194 produce a variety of antimicrobial compounds that may have application in disease control.